Hemodynamic adaptations induced by short-term run interval training in college students - García Suárez, Patricia Concepción (2020)
Perceived lack of time is one of the most often cited barriers to exercise participation. High intensity interval training has become a popular training modality that incorporates intervals of maximal and low-intensity exercise with a time commitment usually shorter than 30 min. The purpose of this study was to examine the effects of short-term run interval training (RIT) on body composition (BC) and cardiorespiratory responses in undergraduate college students. Nineteen males (21.5 ± 1.6 years) were randomly assigned to a non-exercise control (CON, n = 10) or RIT (n = 9). Baseline measurements of systolic and diastolic blood pressure, resting heart rate (HRrest), double product (DP) and BC were obtained from both groups. VO2max and running speed associated with VO2peak (sVO2peak) were then measured. RIT consisted of three running treadmill sessions per week over 4 weeks (intervals at 100% sVO2peak, recovery periods at 40% sVO2peak). There were no differences in post-training BC or VO2max between groups (p > 0.05). HRrest (p = 0.006) and DP (p ≤ 0.001) were lower in the RIT group compared to CON at completion of the study. RIT lowered HRrest and DP in the absence of appreciable BC and VO2max changes. Thereby, RIT could be an alternative model of training to diminish health-related risk factors in undergraduate college students.